Why we need an "ecological ethics". Issue 6 (1st August 2005) - Minteer, Ben A.; Collins, James P.
Abstract : Research ecologists and biodiversity managers frequently have to contend with difficult ethical questions during the course of their work. Yet there is no established approach or field within professional or practical ethics devoted to helping researchers and managers identify and reason through these complex ethical and philosophical issues. Unlike biomedical scientists and clinicians, ecologists and biodiversity managers lack an explicit scholarly forum such as bioethics, that can help them to analyze the complicated ethical situations they encounter in the field, the laboratory, or the conservation facility. Here we present a series of real world cases to illustrate some of the current ethical challenges faced by research ecologists and managers. We call for a new integrated and interdisciplinary field of concrete ethical inquiry – "ecological ethics" – that will fill an important gap in the practical and professional ethics literature, as well as provide ecological researchers and managers with a critical support network and resource base to improve ethical decision making.